y=-3(x-2)(x-7)

Simple and best practice solution for y=-3(x-2)(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=-3(x-2)(x-7) equation:


Simplifying
y = -3(x + -2)(x + -7)

Reorder the terms:
y = -3(-2 + x)(x + -7)

Reorder the terms:
y = -3(-2 + x)(-7 + x)

Multiply (-2 + x) * (-7 + x)
y = -3(-2(-7 + x) + x(-7 + x))
y = -3((-7 * -2 + x * -2) + x(-7 + x))
y = -3((14 + -2x) + x(-7 + x))
y = -3(14 + -2x + (-7 * x + x * x))
y = -3(14 + -2x + (-7x + x2))

Combine like terms: -2x + -7x = -9x
y = -3(14 + -9x + x2)
y = (14 * -3 + -9x * -3 + x2 * -3)
y = (-42 + 27x + -3x2)

Solving
y = -42 + 27x + -3x2

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = -42 + 27x + -3x2

See similar equations:

| 19a-18a+7=-13 | | -6(2+6x)=-120 | | 3x^9y^7+6x^7y^6+9x=0 | | -5(2m-4n)= | | 1/2(8h)=36 | | 6+6(2x-1)=12x | | 2/v=1/8 | | -17=-13-6(4b+20) | | (y-8)+24=3(y-6) | | 15t+6t-11t=150 | | 7x-12x+31x+15x=+12-8 | | (x+59)+(x+51)+84=180 | | -12v+16=4(-3v+4) | | m+5-4=18 | | 5x-2=(14/3) | | 3/4b15 | | 11x-48=5x+10 | | 8n=87 | | 14-5(4f-6)=-3-17-20f | | 24a-22=4a(1-6a) | | 16x^3-12x^2+20x-15= | | 7x+2=7y-10 | | z-2.3=5.1 | | 2/5t=30 | | X^2+15x-160= | | 14s+3s-7s=200 | | 99+90+90+(x^2)=360 | | 4x+3x-x=+2-32+5 | | 3/5x-10=11 | | 2(-8m-16)=-4(4m+8) | | -y+13=-42 | | cos(x)cos(y)dx+sen(x)sen(y)dy=0 |

Equations solver categories